Contextualizing Informal Labeling Effect on Adolescent Recidivism in South Korea - Lee, Jonathan (International journal of offender therapy and comparative criminology, 2018)
Symbolic interactionism argues that the effect of informal labeling by general others, such as family and friends, on behavior depends on the social context under which labeling takes place. Despite abundant research on informal labeling, little effort has been made to contextualize its impact on adolescent reoffending. Also, compared with other theories, only a few studies have been conducted among youths in Asian population. Using three consecutive waves of self-reported survey data from a nationally representative sample of 2,406 Korean adolescents, this study examined an interactional model for the informal labeling effect. Findings suggest that informal labeling, as well as school commitment and delinquent peer association, has an independent effect on delinquency. Also supported is the symbolic interactionist hypothesis that adolescents with greater involvement in delinquent subcultures were less susceptible to informal labeling. Implications of the findings are discussed.